Antipsychotic polypharmacy in older Australians. (10th November 2017) - Kalisch Ellett, Lisa M.; Pratt, Nicole L.; Kerr, Mhairi; Roughead, Elizabeth E.
ABSTRACT: Background: Antipsychotics are commonly used, and the rate of use is highest, among those aged 65 years or over, where the risk of adverse events is also high. Up to 20% of younger adults use more than one antipsychotic concurrently; however there are few studies on the prevalence of antipsychotic polypharmacy in older people. We aimed to analyze antipsychotic use in elderly Australians, focusing on the prevalence of antipsychotic polypharmacy and the use of medicines to manage adverse events associated with antipsychotics. Methods: A cross-sectional study was conducted using Australian Department of Veterans' Affairs (DVA) administrative claims data for the period 1 March 2014 to 30 June 2014. Veterans dispensed at least one antipsychotic medicine during the study period was included. We determined the number of participants dispensed antipsychotic polypharmacy and the number of participants dispensed medicines to manage antipsychotic side effects. Results: There were 7, 412 participants with a median age of 86 years. Fifty-one percent ( n =3, 784) were women and 48% ( n =3, 569) lived in residential aged-care. Fifty one participants (0.7%) were dispensed anticholinergic medicines indicated for the management of antipsychotic-associated extrapyramidal movement disorders and eight (0.1%) were dispensed medicines for the management of hyperprolactinemia. Five percent of participants ( n =365) received dual antipsychotics. Dual antipsychotic users were more likely to be under the care of a psychiatrist or to have had a mental health hospitalization than those using a single antipsychotic. Conclusions: Antipsychotic polypharmacy occurred in one in 20 elderly persons, indicating that there is room for improvement in antipsychotic use in elderly patients.